The Structure of the Graduate Profile Text of the Master of Indonesian Language Education Study Program Which is Accredited as Excellent in Indonesia - Noermanzah, Noermanzah; Yanti, Nafri (IJLECR (International Journal of Language Education and Cultural Review), 2025)
Graduate profiles are very important for study programs in higher education because they serve as the main guideline in developing the curriculum and determining the competencies that graduates must have. Study programs that are accredited as superior usually have graduate profiles that have a clear, systematic, and directed text structure. Therefore, this study aims to describe the structure of the graduate profile text of the Master of Language Education Study Program PLIndonesia which is accredited as superior in Indonesia. The Systemic Functional Linguistics (SFL) method is used to analyze the structure of the graduate profile text of the study program. The data collection technique used is the documentation technique sourced from the website of the Master of Indonesian Language Education Study Program which is accredited as superior in Indonesia. The data analysis technique uses the SFL technique with the following steps: constituent structure, grammatical constituent analysis, and labeling based on class or function. The results of the study show that the structure of the graduate profile text of the Master of Indonesian Language Education Study Program which is accredited as superior in Indonesia is dominated by nominal phrases with a fixed pattern (NP + PrepF) that describe professions and fields of expertise. Functionally, the graduate profile acts as a Subject (S) which contains an implicit predicative meaning according to the main competencies. Furthermore, based on the cognitive levels in Anderson & Krathwohl's taxonomy, it demonstrates high competencies, namely applying, analyzing, and creating, which confirms the profile of Master's graduates as middle-level experts and professionals.